Transformation of the Indonesian National Police's Communication Strategy in Building a Public Narrative through Platform X - Rahmat Edi Irawan; Farikha Rachmawati (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2025)
The acceleration of digital transformation has reshaped how institutions communicate with the public. To remain relevant, both governmental and private organizations must adapt to these shifts—so too must the Indonesian National Police (POLRI). Through the strategic use of social media, particularly Platform X (Twitter), POLRI seeks to cultivate closeness with a public that is increasingly critical, responsive, and participatory. This study investigates how POLRI has transformed its communication strategy to construct a coherent public narrative on Platform X. It focuses on three dimensions: the evolution of work models, new collaboration patterns between the Public Relations Division of POLRI and external digital partners, and the strategic management of hashtags as part of an integrated digital-communication approach. Employing a descriptive-qualitative method, data were collected through interviews with policy-level officials, field implementers, and external partners. The findings reveal a paradigm shift from one-way, hierarchical communication toward an open, two-way participatory dialogue that allows the public to offer feedback, criticism, and direct engagement. This shift is not merely technical but reflects an institutional reconfiguration of strategic communication practices within an algorithm-driven platform environment. By explicitly linking empirical findings with Strategic Communication Theory, this study contributes to the understanding of how public institutions negotiate legitimacy, authority, and visibility within platform-based communication ecosystems. The study concludes that the success of POLRI’s online communication rests not only on message quality but also on institutional synergy, adaptability to algorithmic change, and the capacity to maintain meaningful dialogue with citizens. Strategic communication, when integrated with digital innovation, enables the institution to strengthen trust and legitimacy in the era of participatory media. This study recommends that POLRI enhance its strategic digital communication capacity through algorithm literacy, data-driven engagement, sustained collaboration with external partners, and the development of ethical guidelines to strengthen public trust and institutional legitimacy in digital platforms.